AKTIVITAS ANTIBAKTERI EKSTRAK KAYU MANIS (CINNAMOMUM BURMANNII) TERHADAP PERTUMBUHAN ESCHERICHIA COLI - Eliya Mursyida; Huda Marlina Wati (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Diarrhea is a bowel movement as much as 3 times or more in a day with the consistency of liquid feces, both accompanied by blood and or mucus. Diarrhea is generally caused by some microbes, one of which is Escherichia coli. Cinnamon is a plant that is known to have efficacy as a drug. Cinnamon has its activity as an antimicrobial, as it contains active compounds such as essential oils. The study aims to analyse the antibacterial activity of cinnamon extracts against the growth of Escherichia coli. The research method uses the research design post-test only with control group with the method of diffusion paper discs at concentrations of 25%, 50%, 75% and 100%. Results showed that the cinnamon extract concentration of 100% and 75% had activity in inhibiting the growth of Escherichia coli with a diameter of the 4.85 mm and 3.15 mm inhibitory zones.